Photodynamic Activity of Fullerenes and Other Molecules Incorporated into Lipid Membranes by Exchange. Issue 1 (12th December 2015) - Ikeda, Atsushi
Abstract: An effective exchange method is described whereby liposomal drug carriers of hydrophobic guest biomolecules are used to incorporate the guests into lipid membranes. The exchange method transfers the guest molecule from a cyclodextrin cavity to a liposome in water. Lipid‐membrane‐incorporated fullerenes (LMIC x : x = 60 or 70) prepared by the exchange method have much higher liposomal stability and fullerene water solubility than those prepared by conventional methods. The LMIC60 have high photodynamic activities with respect to human cancer cells under 350–500 nm excitation. Furthermore, the LMIC60 bilayers, containing light‐harvesting antenna molecules in addition to the C60, showed improved activities at the optimal wavelength for photodynamic therapy. Abstract : Photodynamic activity of fullerenes and other molecules incorporated into lipid membranes by exchange : Lipid‐membrane‐incorporated fullerenes prepared by the exchange method have much higher liposomal stability, fullerene water solubility, and photodynamic activity than those prepared by conventional methods.